Deposition of SrZrO3 thin films using liquid delivery metal-organic chemical vapor deposition - Uchiyama, K; Sakairi, H; Shiosaki, T; Kariya, T; Ikeda, H; Yanagimoto, K; Yamada, Y; Nakayama, A (2009)
Proton-conductive SrZrO3 films were successfully deposited on Pt/SiOx/Si and porous stainless-steel substrates by liquid delivery metalorganic chemical vapor deposition (LD-MOCVD). The as-deposited films deposited on the Pt/SiOx/Si substrate at 600 °C showed good crystallinity and post-annealing at temperatures below 800 °C resulted in improved crystallinity. A 200-nm-thick film deposited on the porous stainless-steel substrate was flat and solid and did not show any gas leakage. We consider this deposition technique to be applicable for the fabrication of a new solid oxide fuel cell structure with intermediate-temperature operation. © 2009 The Japan Society of Applied Physics.